Women and Reformation in the Sixteenth-Century Low Countries: A Historiographical Lacuna - Kooi, Christine (Early Modern Low Countries, 2025)
The history of women and their experiences of Reformation in the sixteenth-century Low Countries remains largely unexplored territory, especially compared to the rest of Europe and to the seventeenth century. Why this is the case is something of a puzzle, though it may have to do with available source material. Since the 1980s a handful of works have been published on the subject, mostly falling along confessional lines, with Anabaptist women receiving by far the most scholarly attention. Reformed and Catholic women have received comparatively less attention. This article surveys the current historiography on women’s experience of religious change in the Habsburg Low Countries and offers some suggestions for future research.